Державна політика благополуччя перед викликами глобального масштабу: проблеми соціалізації, соціоекономічна трансформація на тлі впровадження цифровизації та технологій штучного інтелекту. - Галушка, Зоя Іванівна; Галушка, Зоя Іванівна (Чехія, 2024)
In the second decade of the twenty-first century, one of the most notable shifts in capitalism is how its digitization increasingly affects people's methods of living and producing. The article represents an attempt to understand the transformational realities of digital capitalism in the field of political economy. In particular, the phenomenon of the emergence and growth of a new class – the precariat – is considered. The key challenges of the digital era of globalism and their implications for state policy of wellbeing are systematized.
State policy of wellbeing in the face of global challenges: problems of socialization, socio-economic transformation against the background of the introduction of digitalization and artificial intelligence technologies.
Keywords: state policy of public welfare; socialization in conditions of global challenges; socio-economic transformation; digitalization and artificial intelligence.